2019
DOI: 10.1002/jsfa.9986
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics of strawberry (Fragaria x ananassa ‘Camarosa’) fruit from plants grown under osmotic stress conditions

Abstract: BACKGROUND Plants activate defense mechanisms to cope with adverse environmental conditions, leading to the accumulation and / or depletion of general and specialized metabolites. In this study, a multiplatform untargeted metabolomics strategy was employed to evaluate metabolic changes in strawberry fruit of cv. Camarosa grown under osmotic stress conditions. Liquid chromatography‐mass spectrometry (LC‐MS/MS) and gas chromatography‐mass spectrometry (GC‐MS) data from strawberries grown under two water‐deficit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…The reduced phytosterol level in this study indicates that the mulberry under stress conditions activates a distinct pathway as a defense to the stress treatments and may have led to forming other derivatives with a more substantial water holding capacity. The results here agree with the study reported by [49].…”
Section: Lipids and Lipid-like Metabolites Change In Response To Drought Stresssupporting
confidence: 94%
See 3 more Smart Citations
“…The reduced phytosterol level in this study indicates that the mulberry under stress conditions activates a distinct pathway as a defense to the stress treatments and may have led to forming other derivatives with a more substantial water holding capacity. The results here agree with the study reported by [49].…”
Section: Lipids and Lipid-like Metabolites Change In Response To Drought Stresssupporting
confidence: 94%
“…However, our study reveals a decreased level of phytosterol. As an adaptive response to environmental conditions, high terpene synthase (TPS) activity levels increase sterol content [49]. The terpene level in this study was higher, and that TPS might have enhanced the sterol content.…”
Section: Lipids and Lipid-like Metabolites Change In Response To Drought Stressmentioning
confidence: 56%
See 2 more Smart Citations
“…ABA content was also observed to increase in strawberry fruits under saline and drought stresses; however, ABA biosynthesis related genes (FaNCEDs, FaCYP707As, FaGTs, and FaBGs) were mostly upregulated only in drought stressed fruits 25 . Similarly, only the drought stress increased the concentrations of ascorbic acid, sugars, and methylsyringin, whereas salt stress induced the synthesis of amino acids in the fruits 26,70 . A mechanism of salt and drought response in strawberry fruits based on these previous results and the gene expression data from this study is shown in Fig.…”
Section: Discussionmentioning
confidence: 96%